A survey of perceived risk and protective behaviours towards COVID-19 in 2020 in Iraqi Kurdistan - M-Amen, Karwan; Shabu, Sherzad A; Mahmood, Kazhan I; Shabila, Nazar P (The Journal of Infection in Developing Countries, 2023)
Introduction: Human perceptions and behavioural responses to the risk of epidemics have always been crucial factors in studying and containing disease spread. This study aims to assess and understand the risk perception and the behavioural response of a sample of the population in the Kurdistan Region toward COVID-19. Methodology: A self-administered online survey (designed on Google Forms) was designed to get a rapid appraisal of the risk perception and behavioural response of people living in the Iraqi Kurdistan Region about COVID-19 from 17–25 November 2020. Results: A total of 390 individuals responded to the survey. Many respondents (65.6%) recognized COVID-19 as a high or very high threat level. The most frequently applied protective behaviours included avoiding spitting on the ground (76.2%), avoiding contacting ill persons (75.9%) and wearing face masks (75.6%). The main source of information about COVID-19 was Internet news (46.2%), followed by social media (44.9%). Significantly higher perceptions of the threat of COVID-19 were found among females (p = 0.004) and those having family members with chronic diseases (p < 0.001). Conclusions: Understanding the general public’s risk perception toward the COVID-19 infection is essential for determining effective protective measures and can be used to guide proper preventive behaviour.